2013
DOI: 10.3892/br.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of NRF2 gene correlated with decreased FEV1 in lung cancers of smokers

Abstract: Abstract. The metabolism of xenobiotics plays a fundamental role in smoking-related lung function loss and the development of pulmonary disease. An NRF2-dependent response is a key protective mechanism against oxidative stress. In the present study, we evaluated the effect of single nucleotide polymorphisms in NRF2 genes on the level of forced expiratory volume in one second (FEV1) in lung cancers of smokers. We genotyped the status of NRF2 gene polymorphisms in 209 surgically treated lung cancer cases of smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Using an additive model, a significant interaction was identified between rs6726395 (G/G + G/A) genotyped individuals, smoking status and reduced mean FEV 1 in the same Japanese cohort ( p int = 0.010) [23,24]. Similarly, the intronic haplotype rs2364723 C/rs6726395 A was associated with significantly reduced FEV 1 in Japanese smokers with lung cancer [25], supporting work by Siedlinski et al . [26] who found lower FEV 1 levels in the Dutch Vlagtwedde-Vlaardingen cohort of 1152 individuals (p = 0.04; CI −87.3 to −1.7).…”
Section: Genetic Mutations Of Nrf2 and Association With Disease Risksupporting
confidence: 64%
“…Using an additive model, a significant interaction was identified between rs6726395 (G/G + G/A) genotyped individuals, smoking status and reduced mean FEV 1 in the same Japanese cohort ( p int = 0.010) [23,24]. Similarly, the intronic haplotype rs2364723 C/rs6726395 A was associated with significantly reduced FEV 1 in Japanese smokers with lung cancer [25], supporting work by Siedlinski et al . [26] who found lower FEV 1 levels in the Dutch Vlagtwedde-Vlaardingen cohort of 1152 individuals (p = 0.04; CI −87.3 to −1.7).…”
Section: Genetic Mutations Of Nrf2 and Association With Disease Risksupporting
confidence: 64%
“…The Nrf2 pathway is an anti-apoptotic pathway that has been demonstrate do function in many organs, particularly in the central nervous system (5). With a short half-life, Nrf2 is an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 pathway is anti-apoptotic and has multiple functions, including resistance to oxidative stress, regulation of inflammatory injury and relief from calcium overloading ( 4 ). Research findings indicate that Nrf2 regulates downstream molecules to protect nerves, particularly against apoptosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired Nrf2 expression in COPD patients might fail to evoke an appropriate antioxidant response and allow excessive apoptosis resulting in lung tissue destruction and emphysema. A previous cohort study showed that certain polymorphisms of the Nrf2 gene correlated with accelerated limitations in airflow of smokers [ 15 , 16 ]. Subjects with impaired Nrf2 might be related to COPD.…”
Section: Discussionmentioning
confidence: 99%